(untitled) (Experimental biology, 2020)
To improve the clinical and laboratory diagnosis of salmonellosis, the most promising is the practical application of molecular genetic diagnostic methods and, first of all, polymerase chain reaction (PCR), which will allow DNA to be detected in the early stages of the disease. The aim of this work is to develop a PCR method for detecting the DNA of Salmonella enterica bacteria, determining the sensitivity and specificity of the developed method. The creation of a diagnostic method based on classical PCR will make it possible to quickly identify the causative agent of salmonellosis with high accuracy and can be used to control and monitor the spread of this infection in the Republic of Kazakhstan. One of the main components of PCR are oligonucleotide primers. When developing a PCR method for detecting the DNA of the Salmonella enterica bacterium, we designed primers S Inv -1F and S Inv -1R. The developed PCR method is highly specific and sensitive (10 microbial cells / ml) and allows the DNA of Salmonella enterica bacteria to be detected in a sample in 3-4 hours. The results of the presented studies indicate the possibility of using the polymerase chain reaction to detect the DNA of the bacterium Salmonella enterica in samples from a pure culture, as well as in biological material. The informativeness of PCR was shown in the analysis of food products, which in real conditions can make it possible to detect the causative agent of the bacterium Salmonella enterica in the early stages of infection. The creation of a domestic PCR test system adapted to Salmonella enterica circulating in Kazakhstan can be used in the development of measures to improve the epidemiological and epizootic conditions for salmonella infection. Keywords: Salmonella enterica, DNA, PCR, specificity, sensitivity